Two rare hemoglobin variants in the Çukurova Region of Turkey: Hb E-Saskatoon and Hb G-Coushatta - Ahmet Genç; Mehmet Akif Çürük (Turkish Journal of Hematology, 2011)
Hb E-Saskatoon and Hb G-Coushatta are rare hemoglobin variants that are not a health problem. Herein we present a Turkish woman that was diagnosed as homozygous Hb E-Saskatoon (only the second such case reported from Turkey) and a Turkish boy diagnosed as heterozygote Hb E-Saskatoon. Additionally, 2 Turkish sisters diagnosed as heterozygote Hb G-Coushatta are presented.